Pharmacological rescue of cognitive function in a mouse model of chemobrain - Nguyen, Lien D.; Fischer, Tom Tobias; Ehrlich, Barbara E. (Molecular neurodegeneration, 2021)
After chemotherapy, many cancer survivors suffer from long-lasting cognitive impairment, colloquially known as “chemobrain.” However, the trajectories of cognitive changes and the underlying mechanisms remain unclear. We previously established paclitaxel-induced inositol trisphosphate receptor (InsP3R)-dependent calcium oscillations as a mechanism for peripheral neuropathy, which was prevented by lithium pretreatment. Here, we investigated if a similar mechanism also underlay paclitaxel-induced chemobrain.
Gesehen am 11.08.2021